Rapid diagnostic testing of a neonate in a family with hypertrophic cardiomyopathy - H. Ueda; T. Miyamoto; Y. Tsurusaki; G. Minase; N. Matsumoto; K. Sengoku (IMR Press, 2020)
Familial hypertrophic cardiomyopathy (HCM) is a common but severe genetic disease. A pregnant woman with familial HCM was referred to our hospital as both the couple and their families were concerned that the baby would later develop HCM. Therefore, we determined the risk of HCM in the neonate. Using whole-exome sequencing, mutational analysis was performed on the patient, her family members (including her father, mother, sister, and husband), and the neonate. Sanger sequencing was also performed. We found that HCM in this family was caused by a mutation in the cardiac heavy chain β-myosin (MYH7) gene. Encouragingly, the neonate did not carry this MYH7 mutation as the father was also negative. We were able to determine that the neonate had no risk of familial HCM. Obstetricians should consider genetic screening if a pregnant woman has a severe risk of such familial complications. Content: We demonstrated absence of familial HCM in a neonate and suggest appropriate genetic screening in pregnant women with familial complications.